550MPa-grade delayed-cracking-resistant hot-forming aluminum-silicon coated steel plate and manufacturing method thereof

By increasing the oxygen content and inclusions inside the steel plate, forming hydrogen traps and controlling the martensite content, the problem of delayed cracking of 550MPa grade thermoformed steel plates is solved, and its resistance to delay cracking is significantly improved.

CN119956214APending Publication Date: 2025-05-09ANGANG STEEL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510097409.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-05-09

AI Technical Summary

Technical Problem

The 550MPa-grade thermoformed steel plate is prone to hydrogen-induced delayed cracking during long-term placement, mainly due to the synergistic effect of diffusion, aggregation and residual stress of hydrogen atoms.

Method used

By increasing the O content inside the steel plate, increasing the number and density of inclusions such as composite oxides and MnS, it can form more hydrogen traps, inhibit the diffusion and aggregation of hydrogen atoms, and control the martensite content and retain a large amount of ferrite structure to slow down the diffusion of hydrogen atoms.

Benefits of technology

The delay cracking resistance of 550MPa grade steel plate is significantly improved, and the delay cracking time is greater than 200 hours, ensuring the stability and safety of the steel plate in long-term use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005253230630000041
    Figure BDA0005253230630000041
  • Figure BDA0005253230630000051
    Figure BDA0005253230630000051
  • Figure BDA0005253230630000061
    Figure BDA0005253230630000061
Patent Text Reader

Abstract

The invention discloses a 550MPa-grade delayed cracking resistant hot forming aluminum-silicon coating steel plate and a manufacturing method thereof. A steel substrate comprises the following chemical components (Wt%): 0.035 to 0.07 percent of C, 0.1 to 0.25 percent of Si, 1.3 to 1.7 percent of Mn, 0.005 to 0.015 percent of S, 0.005 to 0.016 percent of P, 0.01 to 0.05 percent of Nb, 0.01 to 0.05 percent of Ti, less than or equal to 0.01 percent of Als, 0.001 to 0.003 percent of B, 0.003 to 0.01 percent of Ca and 0.005 to 0.01 percent of O. The steel contains inclusions of composite oxides and MnS, the size of the inclusions is smaller than 500 nm, and the distribution number of the inclusions is 5-15 / mm < 2 >. The manufacturing method comprises the steps that molten steel enters an LF furnace, the temperature is 1620-1660 DEG C, the total oxygen value is 400-600 ppm, the moving-out temperature is 1610-1630 DEG C, oxygen blowing and temperature rising are conducted during the period, the total oxygen content of the molten steel is 80-150 ppm, the total oxygen value of tundish molten steel is 70-130 ppm, the temperature is 1535-1560 DEG C, and then continuous casting, hot rolling, cold rolling, hot dipping and hot stamping forming are conducted. The delayed cracking resistance of the steel plate is further improved by increasing the O content in the steel plate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an oxygen-containing hot-formed aluminum-silicon coated steel plate with excellent 550MPa-level delayed cracking resistance and a manufacturing method thereof, and belongs to the field of hot stamping. Background Art

[0002] Hot pressing technology is currently an ideal and quick way to improve material strength, especially in the automotive field. After the steel plate is heated to the austenitizing temperature, it is kept warm for a certain period of time and quickly stamped into the required part shape in the austenite area, and finally a high-strength part mainly composed of martensite is obtained. However, the oxide layer produced by high-temperature heating cannot meet the subsequent coating process and requires sandblasting and other process treatments, which increases the complexity of the process and brings environmental pressure. The addition of aluminum-silicon coating effectively inhibits the growth of the oxide layer on the surface of the steel plate, and the aluminum-silicon coating only forms a very thin oxide layer through the interdiffusion surface with Fe at high temperature, which does not affect the subsequent painting and other process treatments at all.

[0003] Although this method greatly improves the strength of parts, the residual stress in the finished parts after hot stamping is large. These stresses mainly come from the phase transformation process of the plate, mainly martensitic shear stress and macro residual stress during the rapid cooling deformation process. Martensite structure is the least sensitive to hydrogen embrittlement. Even for 550MPa grade steel, the volume proportion of martensite has reached more than 20%. Delayed cracking is mainly caused by the diffusion and aggregation of H atoms inside the substrate to form H2. After H2 fully grows, it forms brittle points inside the plate under the joint action of residual stress, which is very easy to break. Therefore, the finished parts after hot forming are prone to hydrogen-induced delayed cracking during long-term storage.

[0004] At present, there are many studies on delayed cracking of high-strength steel plates, and the main theories include hydrogen pressure theory and hydrogen-promoted plastic deformation theory. Although there is no single theory that can fully explain this phenomenon, it is generally recognized in the industry that the diffusion, aggregation and synergistic effect of hydrogen atoms and residual stress are the main causes of delayed cracking of high-strength steel plates. Therefore, controlling the diffusion and aggregation of hydrogen atoms is an effective way to solve delayed cracking. Studies have shown that dislocations, grain boundaries, vacancies, and precipitated phases can all become effective hydrogen traps. The smaller the grain size, the more grain boundaries, and when the small-angle grain boundaries are dominant, the more uniform the distribution of hydrogen atoms in the grain boundaries and the less likely they are to aggregate, the lower the probability of hydrogen precipitation; when the vacancies and precipitated phases are small in size, dense dislocation groups are formed around them, which can effectively form hydrogen traps and inhibit the aggregation and precipitation of hydrogen atoms. In the currently commonly used hot-pressed sheets, smaller grain sizes and more grain boundaries are obtained by controlling the original austenite grains; various carbide precipitation phases are formed by the addition of Nb, V, and Ti, which not only inhibits grain growth, but also forms hydrogen traps to varying degrees.

[0005] However, from the actual use, high-strength steel plates, especially hot-pressed plates mainly composed of martensite, still have large residual stress inside. After long-term storage, delayed cracking still occurs under the action of hydrogen evolution reaction. Many delayed cracking occurs after loading, and its potential risk is very high. The diffusion coefficient of H atoms in martensite is significantly higher than that of ferrite, pearlite, austenite, etc. For 550MPa-level low-strength hot-formed steel, there is still 10% to 25% (volume percentage) of martensite phase structure after quenching. From the application point of view, 550MPa-level steel is guaranteed to be used for small-sized and thick-thick connecting components. There is a high content of ferrite inside it, which is deformed with high elongation, but large deformation also brings large residual stress, which can accelerate the aggregation of H atoms in martensite and produce delayed cracking. Therefore, it is very important to control the diffusion of H atoms inside 550MPa-level steel. Summary of the invention

[0006] The object of the present invention is to provide a 550MPa grade delayed cracking resistant hot-formed aluminum-silicon coated steel plate and a manufacturing method thereof, by increasing the O content inside the steel plate to increase the number of inclusions inside the steel plate, thereby further improving the delayed cracking resistance of the steel plate.

[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0008] One of the technical solutions of the present invention is to provide a 550MPa grade delayed cracking resistant hot-formed aluminum-silicon coated steel plate, wherein the mass percentage of each element in the steel substrate is C: 0.035%-0.07%, Si: 0.1%-0.25%, Mn: 1.3%-1.7%, S: 0.005%-0.015%, P: 0.005%-0.016%, Nb: 0.01%-0.05%, Ti: 0.01%-0.05%, Als: ≤0.01%, B: 0.001%-0.003%, Ca: 0.003-0.01%; O: 0.005%-0.01%, and the balance is Fe and unavoidable impurities; the steel contains inclusions of composite oxides and MnS, the size of which is less than 500nm, and the distribution is 5-15 pieces / mm calculated by the cross section. 2 .

[0009] Furthermore, the composite oxide inclusions are Mn-Nb-O(C), Mn-Ti-O(C, Ca), Mn-Nb-O-Al(Si, C, Ca), and Mn-Ti-O-Al(Si, C, Ca), and the steel contains two or more composite oxide and MnS inclusions.

[0010] Furthermore, among the inclusions, those with a size of 50 to 300 nm account for 60% to 70%, and those with a size of 301 to 500 nm account for 30% to 40%.

[0011] Furthermore, the volume percentage of martensite in the steel plate is 13% to 25%, and the rest is ferrite and an inevitable small amount of retained austenite.

[0012] Furthermore, the inclusion exists in a shape approximately like a circle.

[0013] Furthermore, when four-point bending prestressing with 1 times the yield strength is applied and the sample is immersed in a hydrochloric acid solution with a pH of 1, the cracking time is greater than 200 hours.

[0014] The second technical solution of the present invention is to provide a method for manufacturing a 550MPa grade delayed cracking resistant hot-formed aluminum-silicon coated steel plate, including molten steel refining, continuous casting, hot rolling, cold rolling, hot dip and hot stamping forming, specifically:

[0015] Molten steel refining: The temperature of the molten steel entering the LF furnace is 1620-1660℃, the total oxygen value is 400-600ppm, and the temperature of the LF furnace is 1610-1630℃. During this period, oxygen blowing is used to increase the temperature to ensure that the total oxygen content of the molten steel is maintained at 80-150ppm when the LF furnace is removed;

[0016] Continuous casting: The total oxygen value of the molten steel in the tundish is 70-130ppm, and the tundish temperature is 1535-1560℃;

[0017] Hot rolling: billet heating temperature is 1180-1250℃, finishing rolling temperature is 1000-1100℃, final rolling temperature is 920-950℃, and coiling temperature is 650-720℃;

[0018] Cold rolling: The cold rolling reduction rate is controlled at 50% to 75%;

[0019] Hot dip: annealing temperature is 780-850℃, the temperature of the plate entering the aluminum pot is 650-680℃, and the bath temperature is 650-660℃;

[0020] Hot stamping: The aluminum-silicon coated steel plate is heated to 930-950°C, kept at this temperature for 5-8 minutes, air-cooled for 10-15 seconds, and then cooled in the mold at a cooling rate of >50°C / s for stamping, with a holding time of 8-15 seconds.

[0021] Furthermore, after LF refining, the molten steel is fed with Si-Ca wire, the wire feeding speed is ≥3.5m / s, and the wire feeding amount is 100-150m / tank.

[0022] Furthermore, the continuous casting billet drawing speed is 1.0-1.5 m / min, and the continuous casting billet thickness is 200-300 mm.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] Based on the existing technology of setting H traps through Nb and Ti precipitate phases, the present invention increases the number of inclusions in the steel by adding a certain amount of O element, thereby increasing the H traps in the steel to improve the delayed cracking resistance of the steel plate, and strictly controls the type, number and size of the inclusions to avoid affecting the mechanical properties. The inclusions become permanent hydrogen traps by changing the surrounding lattice characteristics, inhibiting the diffusion and aggregation ability of H atoms. At the same time, through the selection of hot pressing process parameters, the content of martensite in the steel is strictly controlled, so that a large amount of ferrite structure exists in the steel. The diffusion coefficient of H atoms in ferrite is much smaller than that of martensite, and the presence of a large amount of ferrite can effectively slow down the delayed cracking time. DETAILED DESCRIPTION

[0025] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other. The described embodiments are only a part of the embodiments of the present invention, not all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] The present invention is described in more detail below through examples.

[0027] The total oxygen content of the hot-formed aluminum-silicon coated steel plate of the present invention is 50-100 ppm, and the inclusions contained are Mn-Nb-O(C), Mn-Ti-O(C, Ca), Mn-Nb-O-Al(Si, C, Ca), Mn-Ti-O-Al(Si, C, Ca) composite oxides, and MnS. The size of the inclusions in the steel plate is less than 500nm, of which the size of 50-300nm accounts for 60%-70%, and the size of 301nm-500nm accounts for 30%-40%, and exists in a shape close to a circle, and the distribution of the inclusions is 5-15 / mm calculated on a plane. 2 , see Table 1 for details.

[0028] Table 1 Inclusions in oxygen-containing hot-formed steel

[0029]

[0030] The mass percentage of each element in the substrate of the hot-formed aluminum-silicon coated steel plate is: C: 0.035% to 0.07%, Si: 0.1% to 0.25%, Mn: 1.3% to 1.7%, S: 0.005% to 0.015%, P: 0.005% to 0.016%, Nb: 0.01% to 0.05%, Ti: 0.01% to 0.05%, Als: ≤0.01%, B: 0.001% to 0.003%, Ca: 0.003 to 0.01%; O: 0.005% to 0.01%, the remainder is Fe and unavoidable impurities, see Table 2 for details. The volume percentage of martensite inside the steel plate is 13% to 25%, and the rest is ferrite and an unavoidable small amount of retained austenite, see Table 6 for details.

[0031] Table 2 Chemical composition of 550MPa grade hot-formed steel (wt%)

[0032] Example C Si Mn S P Nb Ti Ca Als O B 1 0.035 0.11 1.5 0.009 0.011 0.031 0.026 0.003 0.01 0.0069 0.003 2 0.041 0.15 1.3 0.011 0.006 0.033 0.019 0.005 0.006 0.0065 0.002 3 0.053 0.21 1.7 0.015 0.009 0.015 0.05 0.006 0.005 0.0087 0.003 4 0.069 0.25 1.6 0.005 0.015 0.050 0.011 0.01 0.003 0.0053 0.002 5 0.063 0.18 1.6 0.013 0.013 0.019 0.043 0.007 0.006 0.0098 0.001 6 0.067 0.13 1.5 0.013 0.008 0.035 0.033 0.003 0.004 0.0076 0.003 Comparison 1 0.055 0.12 1.5 0.013 0.009 0.033 0.036 0.005 0.03 0.0013 0.003 Comparison 2 0.068 0.18 1.5 0.013 0.007 0.038 0.033 0.006 0.05 0.0011 0.003

[0033] It can be seen from Tables 1 and 2 that, in addition to the traditional Nb and Ti precipitation phases, the hot-formed steel also contains a large number of smaller, nearly circular inclusion particles. The inclusion particles can form effective H traps, inhibit the aggregation and diffusion of H atoms, and improve the delayed cracking performance of the steel plate after hot forming. It can be seen from the composition that the O content in the composition design of this patent is significantly higher than that of traditional hot-formed steel, and the Als content is lower, mainly because O in the steel forms inclusion particles.

[0034] A method for manufacturing a 550MPa-grade delayed cracking resistant hot-formed aluminum-silicon coated steel plate, comprising molten steel refining, continuous casting, hot rolling, cold rolling, hot-dip galvanizing and hot stamping forming, specifically:

[0035] Molten steel refining: The temperature of the molten steel entering the LF furnace is 1620-1660℃, the total oxygen value is 400-600ppm, and the temperature of the LF outflow is 1610-1630℃. During this period, oxygen blowing is used to increase the temperature. When the molten steel is outflowed from the LF furnace, the total oxygen content is maintained at 80-150ppm; after LF refining, the molten steel is fed with Si-Ca wire, the wire feeding speed is ≥3.5m / s, and the wire feeding amount is 100-150m / tank. See Table 3 for details.

[0036] Table 3 Steelmaking process parameters of 550MPa hot-formed steel

[0037]

[0038] Continuous casting: The total oxygen value of the molten steel in the tundish is 70-130ppm, the tundish temperature is 1535-1560℃, the billet drawing speed is 1.0-1.5m / min, and the continuous casting billet thickness is 200-300mm. See Table 4 for details.

[0039] Table 4 Continuous casting process parameters of 550MPa hot-formed steel

[0040]

[0041] Hot-dip rolling: billet heating temperature 1180-1250℃, finishing rolling temperature 1000-1100℃, final rolling temperature 920-950℃, coiling temperature 650-720℃; cold rolling reduction rate controlled at 50%-75%; continuous annealing temperature 780-850℃, plate temperature entering aluminum pot 650-680℃, plating solution temperature 650-660℃. See Table 5 for details.

[0042] Table 5 Rolling and hot-dip coating process of 550MPa grade hot-formed steel

[0043]

[0044] Hot stamping: The aluminum-silicon coated steel plate is heated to 930℃~950℃, kept at this temperature for 5~8min, air-cooled for 10~15s, and then cooled in the mold at a cooling rate of >50℃ / s, and the holding time is 8~15s. See Table 6 for details.

[0045] Table 6 Hot forming process of 550MPa grade hot forming steel

[0046]

[0047] It can be seen from Tables 3 to 6 that oxygen-containing hot-formed steel mainly controls the oxygen content in the steel by passing oxygen through the LF furnace in the steelmaking process. The O value is significantly increased compared with traditional hot-formed steel, and a large number of tiny oxygen-containing inclusion particles are formed in the final product, which can form permanent H traps.

[0048] The coated steel plate was prestressed by four-point bending with 1 times the yield strength and immersed in a hydrochloric acid solution with a pH of 1. The cracking time was greater than 200 hours. See Table 7 for details.

[0049] Table 7 Delayed cracking measurement fracture time h PH = 1 four-point bending - prestress is 1 times the yield strength

[0050]

[0051] As can be seen from Table 7, the delayed cracking time in oxygen-containing hot-formed steel is significantly longer than that in conventional hot-formed steel.

[0052] Based on the existing technology of setting H traps through Nb and Ti precipitation phases, the present invention increases the number of inclusions in the steel plate by increasing the O content inside the steel plate, sets more traps for the diffusion of H elements in the steel, suppresses the diffusion and aggregation of H atoms, and strictly controls the size of inclusions to avoid affecting the mechanical properties; in the hot forming and stamping process, the martensite content is controlled, a large amount of ferrite structure is retained, and the low diffusion rate of H atoms in ferrite is used to assist in suppressing the diffusion and aggregation of H atoms, thereby further improving the delayed cracking resistance of the steel plate.

[0053] The above embodiments are only for illustrating the technical concept and features of the present invention, but not for limiting the present invention. The purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A 550MPa grade delayed cracking resistant hot-formed aluminum-silicon coated steel plate, characterized in that: The mass percentage of each element in the steel substrate is: C: 0.035% to 0.07%, Si: 0.1% to 0.25%, Mn: 1.3% to 1.7%, S: 0.005% to 0.015%, P: 0.005% to 0.016%, Nb: 0.01% to 0.05%, Ti: 0.01% to 0.05%, Als: ≤0.01%, B: 0.001% to 0.003%, Ca: 0.003% to 0.01%, O: 0.005% to 0.01%, and the balance is Fe and unavoidable impurities; the steel contains inclusions of composite oxides and MnS, the size of which is less than 500nm, and the distribution is 5 to 15 / mm calculated by cross section. 2 .

2. The 550MPa delayed cracking resistant hot-formed aluminum-silicon coated steel plate according to claim 1, characterized in that: The composite oxide inclusions are Mn-Nb-O(C), Mn-Ti-O(C, Ca), Mn-Nb-O-Al(Si, C, Ca), and Mn-Ti-O-Al(Si, C, Ca). The steel contains composite oxides and MnS inclusions of two or more kinds.

3. The 550MPa delayed cracking resistant hot-formed aluminum-silicon coated steel plate according to claim 1, characterized in that: Among the inclusions, those with a size of 50 to 300 nm account for 60% to 70%, and those with a size of 301 to 500 nm account for 30% to 40%.

4. The 550MPa delayed cracking resistant hot-formed aluminum-silicon coated steel sheet according to claim 1, characterized in that: The volume percentage of martensite in the steel plate is 13% to 25%, and the rest is ferrite and an inevitable small amount of retained austenite.

5. The 550MPa delayed cracking resistant hot-formed aluminum-silicon coated steel plate according to claim 1, characterized in that: The inclusions exist in a substantially circular shape.

6. The 550MPa delayed cracking resistant hot-formed aluminum-silicon coated steel plate according to claim 1, characterized in that: Using four-point bending prestressing loading of 1 times the yield strength and immersion in a PH=1 hydrochloric acid solution, the cracking time is greater than 200 hours.

7. A method for manufacturing a 550MPa delayed cracking resistant hot-formed aluminum-silicon coated steel sheet according to any one of claims 1 to 6, comprising molten steel refining, continuous casting, hot rolling, cold rolling, hot dip coating and hot stamping, characterized in that: Molten steel refining: The temperature of the molten steel entering the LF furnace is 1620-1660℃, the total oxygen value is 400-600ppm, and the temperature of the LF furnace is 1610-1630℃. During this period, oxygen blowing is used to increase the temperature to ensure that the total oxygen content of the molten steel is maintained at 80-150ppm when the LF furnace is removed; Continuous casting: The total oxygen value of the molten steel in the tundish is 70-130ppm, and the tundish temperature is 1535-1560℃; Hot rolling: billet heating temperature is 1180-1250℃, finishing rolling temperature is 1000-1100℃, final rolling temperature is 920-950℃, and coiling temperature is 650-720℃; Cold rolling: The cold rolling reduction rate is controlled at 50% to 75%; Hot dip: annealing temperature is 780-850℃, the temperature of the plate entering the aluminum pot is 650-680℃, and the bath temperature is 650-660℃; Hot stamping: The aluminum-silicon coated steel plate is heated to 930-950°C, kept at this temperature for 5-8 minutes, air-cooled for 10-15 seconds, and then cooled in the mold at a cooling rate of >50°C / s for stamping, with a holding time of 8-15 seconds.

8. The method for manufacturing a 550MPa delayed cracking resistant hot-formed aluminum-silicon coated steel plate according to claim 7, characterized in that: After LF refining, the molten steel is fed with Si-Ca wire, the wire feeding speed is ≥3.5m / s, and the wire feeding amount is 100-150m / tank.

9. The method for manufacturing a 550MPa delayed cracking resistant hot-formed aluminum-silicon coated steel sheet according to claim 7, characterized in that: The continuous casting billet drawing speed is 1.0-1.5 m / min, and the continuous casting billet thickness is 200-300 mm.